Study of Multiplicative Sequence of Pseudorandom Frames in a Knowledge Base - Sidnyaev, N. I.; Sineva, E. E. (Automatic documentation and mathematical linguistics, 2025)
This paper describes models of knowledge representation in intelligent systems, namely frames, that allow a knowledge hierarchy to be organized. Basic information on random and pseudorandom sequences and their use, obtainment, and testing in knowledge bases is presented. Particular attention is paid to different types of generators, the quality control of the output sequences, and the potential for their use in the cryptographic protection of knowledge bases. Frames extend the potential of intelligent systems, holding entities as structured objects that have named cells and associated values. This article examines the peculiarities of the functioning of intelligent systems using frames.